ANALISIS DEFORESTASI DI TAMAN NASIONAL KERINCI SEBLAT STUDI KASUS DESA RENAH PEMETIK MENGGUNAKAN PENDEKATAN PENGINDERAAN JAUH - rian, andrian; Ramadhan, Risky (JURNAL BUANA, 2024)
This study aims to determine deforestation in the Kerinci Seblat National Park in Renah Picker Village from 2014 to 2022. The method used in this study is a quantitative descriptive method with a remote sensing approach. The research results show that from 2014 to 2022 there has been a conversion of forest area land into plantation land covering an area of 9,217.25 ha. The details are forest areas and the Zoning Area of the Kerinci Seblat National Park which have been affected by deforestation as follows: Production forest The area of forest affected by deforestation is 1,844.19 hectares, Forest in the National Park There is an area of 6.44.96 hectares that has experienced deforestation, there is also a National Park Zoning area that has experienced deforestation as follows: Core Zone The area affected by deforestation is 713.12 hectares, Rehabilitation Zone The area affected deforestation of 1,426.29 hectares, and the Jungle Zone The area affected by deforestation is 4,505.53 hectares